The discourse of technological acceleration: The development of vision pro through the lens of Paul Virilio - Pratama, Tito Ari (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2024)
This study examines the potential and impact of Virtual Reality (VR), focusing on Apple's Vision Pro innovation. A phenomenological approach was employed to analyze the social and cultural implications of VR adoption through surveys, interviews, and online observations. Findings reveal that while VR holds significant potential in education and communication, its adoption in Indonesia faces barriers due to limited public understanding. Vision Pro blurs the boundaries between the real and virtual worlds, raising ethical and social challenges. Using Paul Virilio's concept of dromology, the study evaluates the rapid technological acceleration that influences identity and social interactions. The study concludes that public awareness and appropriate supervision are essential to ensure the safe and beneficial use of VR. Technologies like Vision Pro have immense potential, but their management must address social and cultural implications to mitigate negative impacts.